Bioorthogonal release of sulfonamides and mutually orthogonal liberation of two drugs. Issue 100 (27th November 2018) - Shao, Zhuzhou; Liu, Wei; Tao, Huimin; Liu, Fang; Zeng, Ruxin; Champagne, Pier Alexandre; Cao, Yang; Houk, K. N.; Liang, Yong
Abstract : Mutually orthogonal click-release pairs—sydnonimine–DIBAC and tetrazine–ABNBD, realize the release of sulfonamide and primary amine drugs selectively and simultaneously in one system. Abstract : Sulfonamide derivatives have been used in pharmaceutics for decades. Here we report a new approach to release sulfonamides efficiently using a bioorthogonal reaction of sulfonyl sydnonimines and dibenzoazacyclooctyne (DIBAC). The second-order rate constant of the cycloaddition reaction can be up to 0.62 M −1 s −1, and the reactants are highly stable under physiological conditions. Most significantly, we also discovered the mutual orthogonality between the sydnonimine–DIBAC and benzonorbornadiene–tetrazine cycloaddition pairs, which can be used for selective and simultaneous liberation of sulfonamide and primary amine drugs.